The effect of fresh frozen plasma in critically ill patients. Issue 5 (May 2017) - Vibede, E.; Hvas, C. L.; Tønnesen, E.; Hvas, A.‐M.
Abstract : Background: Critically ill patients often receive fresh frozen plasma (FFP) if they have abnormal conventional coagulation tests. The aim of this study was to investigate the effect of FFP transfusion judged by a wide range of coagulation tests. Methods: We included 30 critically ill patients receiving FFP and 30 critically ill patients who did not receive FFP. For patients receiving FFP, blood samples were obtained before and 1 h after FFP transfusion. Conventional coagulation tests, thromboelastometry (ROTEM ®, EXTEM, INTEM and FIBTEM) and thrombin generation were performed. Systematic recording of vital signs was performed for all patients. Results: The median values of the conventional coagulation tests were abnormal before and after FFP (PT: (normal > 0.6) median 0.3 before vs. 0.3 after; INR: (normal < 1.2) median 2 before vs. 1.7 after; APTT: (normal < 38 s) median 45 s before vs. 42 s after). Eight of nine ROTEM ® parameters were within the reference interval judged by median values before FFP transfusion, and all median parameters were within the reference interval after FFP transfusion. Median in three of four thrombin generation parameters was within the reference interval both before and after FFP transfusion. Conclusion: Patients presented abnormal conventional coagulation tests both before and after FFP transfusion. In contrast, ROTEM ® and thrombin generation parameters were mainly within the reference interval both before and after FFP transfusion. FFP transfusions caused only negligible, although statically significant, improvements on coagulation measurements judged by conventional coagulation tests, ROTEM ® and thrombin generation.